"בְּלַאי בָּלוּם זֶה. הַבְּלַאי הַבָּלוּם וְהֶעָלוּם: על האובייקטים בשירת אבות ישורון - לבנון, שחר (מכאן, 2024)
This article examines the objects in the poetry of Avot Yeshurun, and shows that their representation in his work can be understood not only from a symbolic point of view, but also from a material perspective. By analyzing four items—scrap metal, a flowerpot, a roof, and letters—the article highlights Yeshurun’s wide range of representations that challenge the binary opposition between symbol and object. Levanon argues that rather than focusing on either the symbolic or material aspect of the poet’s treatment of the thing, it would be more fruitful to consider the movement between these categories as a fundamental feature of this poetry. In his analysis of the object, Levanon draws on the methodological vocabulary of affect theory, as well as artistic techniques such as found object and readymade.Rather than analyzing objects and subjects as separate, rigid categories, affect theory explores the relational aspect between them, focusing on their dynamic, durational, fluid, and liminal nature. Levanon shows that Yeshurun’s work moves along a spectrum of representation that does not fixate on a particular poetic position; instead, it captures a moment in which object and subject are intertwined and bleed into one another. In this way, Yeshurun blurs the distinction between subject and object and creates intersubjective relations between them.